اسلام اور ہندومت میں سوگ سے متعلق عقائد و رسومات کا تقابلی جائزہ (Al-Aasar, 2026)
This research presents a comparative study of the beliefs and rituals related to mourning and post-death practices in Islam and Hinduism. Death, as an inevitable and fundamental part of human life, has been a subject of contemplation across cultures and religions. In both Islam and Hinduism, mourning (soag) is a significant aspect of how individuals cope with the loss of loved ones. Islam emphasizes patience, acceptance, and prayer during mourning, with clear prohibitions on practices such as wailing, self-harm, and prolonged mourning. The mourning period in Islam is strictly defined, typically lasting three days, with special consideration for widows, who observe a designated waiting period (iddah). In contrast, Hinduism views death as a transition, where the soul’s journey continues through karma and reincarnation. The mourning rituals in Hinduism are elaborate, lasting up to thirteen days, and are linked to the spiritual well-being of the deceased’s soul and their family. This study explores the doctrinal differences and commonalities between the two religions regarding post-death mourning practices, with a focus on their impact on social and cultural integration. The research aims to bridge the knowledge gap by providing a clear understanding of these religious practices, promoting interfaith harmony, and contributing to a deeper understanding of religious diversity in South Asia.